Práticas informacionais em contexto museológico: o Museu Casa de José Américo - Silva, Tahis Virgínia Gomes da (2011)
Information Science and Museology show openness to dialogue discipline. Both areas interested in the museum exhibitions (LOUREIRO, LOUREIRO, SILVA, 2008; MORAES, 2008) included as the main vehicle for creating social significance of the museum. This thesis aims to analyze the narrative exposition of the Casa of José Américo Museum (CJA) from the characterization of the formation and operation of its expository structures, while information practices, characterized as a descriptive analysis of character too, exploratory approach outlined as a field study (Gil, 2006). It addresses the following themes: information; dialogical relation of Information Science, Museology and Semiotics, Memory and Collective Identity, Culture Heritage Material; Typologies Museum, emphasizing the Houses-Museum, museum exhibitions and Informational Practices in museological context. The research is the permanent exhibition at the Casa of José Américo Museum, located in the city of João Pessoa - PB, whose collection represents the life and work of writer and politician José Américo. It is used as a research method to Semiotic Analysis. To collect data we used the technique of direct observation and qualitative non - participatory and non-directed and informal interviews with museologist who planned and assembled the exhibition of the Museum CJA. It is concluded that exposure can be studied as a museum and field research object, understanding it as a space for dissemination of information, representing the social and cultural role of the museum. Understanding how memory representation (DIEHL, 2002) one can see that Semiotics, both as theory and as a research method, is the theory that underlies this representational process, since it is given both in the context of materiality - sign object, sign vehicle - as in the immateriality - interpretant sign. Therefore, the analysis of informational phenomena, focusing on the collective cultural memory, pervades the relationship with the semiotic analysis, through which you can build methodological models for the study of information as memory support. Understand the museums as producers of information and construction of representations from fragments of reality represented there in the material culture expressed in the exhibits is to see the museum as a place of production of meaning.